Automated Synthesis of a 184-Member Library of Thiadiazepan-1, 1-dioxide-4-ones - Fenster, Erik (2011)
[Image: see text] The construction of a 225-member (3 × 5 × 15) library of thiadiazepan-1,1-dioxide-4-ones was performed on a Chemspeed Accelerator (SLT-100) automated parallel synthesis platform, culminating in the successful preparation of 184/225 sultams. Three sultam core scaffolds were prepared based upon the utilization of an aza-Michael reaction on a multifunctional vinyl sulfonamide linchpin. The library exploits peripheral diversity in the form of a sequential, two-step [3 + 2] Huisgen cycloaddition/Pd-catalyzed Suzuki–Miyaura coupling sequence.